Identity and productive restructuring in the Açu-Mossoró and Sertão do Apodi territories of Rio Grande do Norte, Brazil: Identidade e reestruturação produtiva nos territórios Açu-Mossoró e Sertão do Apodi, no Rio Grande do Norte - Nunes, Emanoel Márcio; Gondim, Maria de Fátima Rocha; da Silva, Márcia Regina Farias (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2019)
The objective of this study is to analyze the territorial policies introduced from a multidimensional perspective of local identities as instruments that give new meaning to or dynamize the Açu-Mossoró and Sertão do Apodi territories, from Rio Grande do Norte state, Brazil. The methodology, developed for the entire country by the Department of Territorial Development of the Ministry of Agrarian Development (SDT/MDA), was based in particular on the comparison of the two territories, considering the indicators of identity and the production of space, derived from the economic activities that contributed over time to the construction of the elements of identity. As a result, it was verified that the productive identity of the Açu-Mossoró and Sertão do Apodi territories changed through a process of productive restructuring that has reconfigured space and the relations between actors. On the other hand, regional policies introduced in the 1980s, which relegated to this space a dismantling of local identities and the construction of dependence and exclusion for many family farmers. But, this context was reversed beginning in the years 1990-2000, according to the perception of the interviewees, by territorial policies that seek to consider the collective capacity of the actors, to restore and value their territorial identities.Keywords: restructuring; family farming; territorial identity; territory.NUNES, Emanoel Márcio; GONDIM, Maria de Fátima Rocha; SILVA, Márcia Regina Farias da. Identidade e reestruturação produtiva nos territórios Açu-Mossoró e Sertão do Apodi, no Rio Grande do Norte. Estudos Sociedade e Agricultura, v. 27, n. 1, p. 137-166, fev. 2019.Submitted in february 2018.Accepted in december 2018.